Positioning the Retail Format in the Dynamic Russian Markets - The Impact of Psychic Distance on the Strategic Choice of a Finnish Retailer - Öling, Veronika (My University, 2006)
The aim of the study was to clarify the strategic positioning of a Finnish retailer operating in the dynamic Russian retail markets. The outcomes of managerial decision making in relation to format element modifications in the transfer of retail format transfer abroad were analyzed. The managerial perception of the psychic distance was applied as the explanatory factor behind the perceived need to modify the retail format elements in the strategic positioning. The theoretic part of the study opened with a general definition of retailing. It carried on with elaborating on the retail format elements being the target of possible modification, as well as on the characteristics of international retailing. The study then proceeded with the theories relevant to retail format transfer, and with a description of the operational context – the Russian retail markets. The empirical part of the study was conducted as a single-case qualitative study, gathering the empirical material by the means of interviewing the manager of foreign operations of the case company. The empirical data gathering was conducted as a half-structured interview. Based on the findings of the study, major modifications to the retail format elements weren’t applied by the Finnish retailer to his Russian operations, even though the perceived psychic distance seems to be considerable. However, some minor modifications were made as to ensure that the company’s Russian strategy would correspond with its overall service-differentiation positioning strategy. This implies that the company pursues a multinational strategy, replicating its existing formula but emphasizing the importance of a limited adaptation to host country markets.
Keywords: International retailing; format positioning; psychic distance; Russia; strategic choice; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|